Phenytoin induced drug rash with eosinophilia and systemic symptoms syndrome: a case report - Devaraj, Yogesh; Belagola, Sathyanarayana Dasegowda; Mukunda, Ranga Swaroop; Manchukonda, Ravi Shankar; Basavanaik, Puneetha; Hasanabba, Aneesa K.; Kumari, Priyanka (International Journal of Basic & Clinical Pharmacology, 2016)
DRESS syndrome (drug rash with eosinophilia and systemic symptoms) is a severe adverse drug reaction characterised by rash, fever, lymphadenopathy and internal organ involvement. Although the death rate can reach 10%, rapid diagnosis and prompt withdrawal of the offending drug is the key to limit morbidity and mortality. The potential role of corticosteroids remains controversial. We report a case of a 45-year-old male patient who suffered a head injury, for which he was prescribed phenytoin. Five weeks later he developed features of DRESS syndrome including facial and peri-orbital oedema, generalized erythematous, maculo-papular rash, conjunctivitis, inguinal lymphadenopathy, leucocytosis, eosinophilia and elevated liver enzymes. Skin biopsy revealed acanthosis and spongiosis of epidermis and dense inflammatory cell infiltrate comprising eosinophils and lymphocytes. In this case, causalty assessment using Naranjo adverse drug reaction probability scale showed that phenytoin was a probable cause for the adverse drug reaction (score-7). Phenytoin was immediately stopped and patient was treated with systemic corticosteroids. The patient improved dramatically within the next few days. Early recognition of symptoms of DRESS and immediate withdrawal of the offending drug followed by prompt treatment with corticosteroids and other supportive measures will ensure quick recovery and will avoid fatal outcomes.